Influence of elevated river flow on hypoxia occurrence, nutrient concentration and microbial dynamics in a tropical estuary - Edmund, Ui Hang Sim; Choon, Weng Lee; Joon, Hai Lim; Pei, Li Heng; Nurul Fitrah, Marican; Kumaran, Narayanan; Chui, Wei Ben (Springer, 2020)
We sampled the Klang estuary during the inter-monsoon and northeast monsoon period (July– Nov 2011, Oct–Nov 2012), which coincided with higher rainfall and elevated Klang River flow. The increased freshwater inflow into the estuary resulted in water column stratification that was observed during both sampling periods. Dissolved oxygen (DO) dropped below 63 μM, and hypoxia was observed. Elevated river flow also transported dissolved inorganic nutrients, chlorophyll a and bacteria to the estuary. However, bacterial production did not correlate with DO concentration in this study. As hypoxia was probably not due to in situ heterotrophic processes, deoxygenated waters were probably from upstream. We surmised this as DO correlated with salinity (R2 = 0.664, df = 86, p < 0.001). DO also decreased with increasing flushing time (R2 = 0.556, df = 11, p < 0.01), suggesting that when flushing time (> 6.7 h), hypoxia could occur at the Klang estuary. Here, we presented a model that related riverine flow rate to the post-heavy rainfall hypoxia that explicated the episodic hypoxia at Klang estuary. As Klang estuary supports aquaculture and cockle culture, our results could help protect the aquaculture and cockle culture industry here.